La necesidad de incorporar el cambio climático en las políticas de desarrollo - García Vargas, Julio (2007)
Climate change is considered the most important global threat facing the human race in this century. Due to the excessive emission of greenhouse gases, the global average temperature is increasing thus altering climate systems and raising the sea level. Although developing countries do not contribute signifi cantly to these emissions, they suffer most of their effects. Peru is particularly vulnerable to the impacts of climate change because most of its resources and productive factors such as fi shing, agriculture and transport are climate sensitive. Combined with the challenge and opportunity of ensuring sustainable development in a complex territory in terms of land and population, this vulnerability forces us to include considerations in national policies aimed at reducing the risk of disasters and climate change adaptation. We now have the Hyogo Framework for Action approved by 168 countries.